Estado nutricional y anemia en infantes menores de 48 meses de cuatro centros infantiles de la ciudad de Loja 2016 - Capa Contento, Gabriela Elizabeth (2018)
Abstract:To identify nutritional status and anemia in children younger than 48 months of four children's centers in Loja city in 2016, a correlational, quantitative and cross-sectional study was performed to determine the anthropometric measures of weight, height, body mass index, and serum hemoglobin in that population, and it was analyzed according to baseline values established by the World Health Organization for age and sex, the United Nations Fund for Childhood classification and the percentage of weight for height (IPT). The Pearson correlation coefficient was used to establish a correlation between nutritional status and hemoglobin values. As a result, 131 children, mostly eutrophic, were studied; the most frequent alteration was overweight, followed by obesity and mild desnutrition; Children without anemia predominated, a condition that was present only in 12,97%. Finally, there was no statistically significant correlation between nutritional status and hemoglobin.